Penerapan Daerah Kerja Pejabat Pembuat Akta Tanah Satu Wilayah Provinsi - Firdaus Akbar; Syahriati Fakhriah; M. Adi Saputra; Sarah (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This research is entitled "Implementation of PPAT Working Areas in Relation to Making Authentic PPAT Deeds in One Province". But in reality PPAT can only work in one district/city, referring to the old regulations. And the Decree of the Minister of Land Affairs and Spatial Planning/Head of the National Land Agency concerning the Appointment and Appointment of Work Areas as Land Deed Making Officials (PPAT) in 2017 is still in one district/city even though the Government Regulation has been in place in 2016. PPAT is a partner of BPN in terms of land registration, BPN only provides one district/city online tool. Henceforth, the Implementing Regulation as the implementation of the PPAT working area in relation to making an authentic PPAT deed in one province has not yet been established. The author obtained data directly by interviewing sources related to "Implementation of PPAT Work Areas in Relation to Making Authentic PPAT Deeds in One Province" and obtained data from literature studies in the form of literature, books, journals, laws and regulations. Scientific works and other reading sources. So with this, the discussion of the thesis focuses on the formulation of the problem. First, how the implementation of the PPAT work area is a province. Second, what is an obstacle in implementing the PPAT work area is one province